2013
DOI: 10.1016/j.econlet.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Taxation and the asymmetric adjustment of selected retail energy prices in the UK

Abstract: This paper investigates the adjustment of the prices of four key petroleum products in the UK following changes in the price of crude oil. We find significant evidence that the pre-tax prices of diesel, kerosene and gas oil adjust more rapidly in an upward than a downward direction but that the pre-tax price of unleaded petrol adjusts symmetrically. However, these patterns are obscured at the pump once one accounts for fuel duty and value added tax, raising the possibility that firms can use the tax system to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 14 publications
10
54
1
Order By: Relevance
“…This observation is consistent with Borenstein et al (1997, pp. 332-334) and We followed the general-to-specific approach recommended by Shin et al (2013) and selected the final ARDL specification for linear and nonlinear (asymmetric) versions. The estimated specification is chosen by starting with max p=13 max q=13 and selecting the optimal lag length using Akaike info criterion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This observation is consistent with Borenstein et al (1997, pp. 332-334) and We followed the general-to-specific approach recommended by Shin et al (2013) and selected the final ARDL specification for linear and nonlinear (asymmetric) versions. The estimated specification is chosen by starting with max p=13 max q=13 and selecting the optimal lag length using Akaike info criterion.…”
Section: Resultsmentioning
confidence: 99%
“…The NARDL approach we applied was used in a context of APT research previously, e.g. Atil et al (2014), Bagnai & Ospina (2015), Chattopadhyay & Mitra (2015), Greenwood-Nimmo & Shin (2013), with a very promising results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the disaggregation of the data allowed the study to show that the asymmetry is not a national problem [17]. Some other studies show that there is no evidence of price asymmetry [18][19][20][21][22]. On the same topic Venditti [23] found that there is some compelling evidence of asymmetries in the adjustment of retail gasoline prices for the U.S. but such evidence appears to be quite mixed for the Euro area.…”
Section: Literature Reviewmentioning
confidence: 87%